2022
DOI: 10.1111/jocd.15438
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of hereditary angioedema on multiparous women

Abstract: Objective Significant concerns for patients with hereditary angioedema (HAE) include hormonal fluctuations and drug safety during pregnancy. The impact of the disease on childbearing in multiparous women remains to be elucidated. We aimed to investigate the clinical course and impacts of multiparity on HAE patients. Study design This observational study included 15 multiparous women with HAE; a total of 88 pregnancies were assessed using a questionnaire and the patient's medical records. Results The median age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Gabriel et al (2022) studied 26 women with 37 pregnancies and reported a rate comparable to that of women without HAE, with eight cases of spontaneous abortion [ 4 ]. Karabiber et al (2022) investigated 88 pregnancies in women with HAE, resulting in 72 healthy babies but noted 12 spontaneous abortions, three stillbirths, and one neonatal death [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gabriel et al (2022) studied 26 women with 37 pregnancies and reported a rate comparable to that of women without HAE, with eight cases of spontaneous abortion [ 4 ]. Karabiber et al (2022) investigated 88 pregnancies in women with HAE, resulting in 72 healthy babies but noted 12 spontaneous abortions, three stillbirths, and one neonatal death [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…The existing literature on the association between HAE and pregnancy loss is limited and offers conflicting findings. 2022) investigated 88 pregnancies in women with HAE, resulting in 72 healthy babies but noted 12 spontaneous abortions, three stillbirths, and one neonatal death [5].…”
Section: Discussionmentioning
confidence: 99%